2021
DOI: 10.21203/rs.3.rs-280297/v1
|View full text |Cite
Preprint
|
Sign up to set email alerts
|

Epidemiological investigation reveals local transmission of SARS-CoV-2 lineage P.1 in Southern Brazil

Abstract: Since its detection in December of 2020, the SARS-CoV2 lineage P.1, descendent of B.1.1.28 lineage, has been identified in several places in Brazil and abroad. This Variant of Concern was considered highly prevalent in Northern Brazil and now is rapidly widening its geographical range. In this short communication, we present epidemiological and genomic information of the first case of P1 lineage in Rio Grande do Sul state, in a patient with no reported travel history and a tracked transmission chain. These fin… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
18
0

Year Published

2021
2021
2021
2021

Publication Types

Select...
5
4

Relationship

2
7

Authors

Journals

citations
Cited by 12 publications
(18 citation statements)
references
References 10 publications
(10 reference statements)
0
18
0
Order By: Relevance
“…Genomic surveillance by the central state laboratory confirmed the predominance of these lineages across RS, following a distribution similar to that observed in other Brazilian states, but revealed that lineage P.2, first detected in October 2020, had been gradually replacing these as the predominant variant as of 31 January 2021 [6]. Lineage P.1 was first detected in RS state in a single clinical specimen obtained on 01 February 2021 from a resident of Gramado, a popular tourist destination in RS, who however, had no history of travel or contact with returning travellers from northern Brazil [2]. Whole genome sequencing in the current study detected a specimen with SARS-CoV-2 P.1 lineage from January 2021.…”
Section: Discussionmentioning
confidence: 95%
See 1 more Smart Citation
“…Genomic surveillance by the central state laboratory confirmed the predominance of these lineages across RS, following a distribution similar to that observed in other Brazilian states, but revealed that lineage P.2, first detected in October 2020, had been gradually replacing these as the predominant variant as of 31 January 2021 [6]. Lineage P.1 was first detected in RS state in a single clinical specimen obtained on 01 February 2021 from a resident of Gramado, a popular tourist destination in RS, who however, had no history of travel or contact with returning travellers from northern Brazil [2]. Whole genome sequencing in the current study detected a specimen with SARS-CoV-2 P.1 lineage from January 2021.…”
Section: Discussionmentioning
confidence: 95%
“…This resulted in the collapse of the state healthcare system [1]. Community transmission of severe acute respiratory syndrome coronavirus 2 (SARS-CoV-2) P.1 lineage was documented in a highly visited RS municipality 1 week before week 6 [2]. We thus investigated whether the P.1 variant of concern (VOC) could be detected in patient specimens from February 2021 in a large tertiary care hospital (830 beds) in RS, which serves also as a COVID-19 referral centre in the state capital, Porto Alegre.…”
mentioning
confidence: 99%
“…In the Amazonas state, a collapse of the health system was observed, which made it difficult to assess the real impact of the P.1 variant on the lethality by covid-19, which may have increased due to the overload of the health system and not exclusively by the intrinsic characteristics of the variant[2]. The emergence of variant P.1 in the RS state was confirmed by the virus identification from a patient with no travel history and presenting symptoms beginning on January 29 (EW 4/2021)[6]. In the following weeks there was a sudden increase in cases of covid-19 in several regions of the state, simultaneously.…”
Section: Introductionmentioning
confidence: 99%
“…Our molecular clock analysis supported this scenario. Another study, once thought to be the first P.1 report in RS, documented local transmission of P.1 from a person who had close contact with tourists and was positive to COVID-19 in early February 2021 (21). This happened in the city of Gramado, a town on the mountains that receives around 6.5 million tourists every year and belongs to the Caxias do Sul intermediate region.…”
Section: Discussionmentioning
confidence: 97%